Synthesis and Swelling Kinetics of Superabsorbent Rice Straw Cellulose Graft Copolymers - Helmiyati; Saefumillah, Asep; Yulianti, Wina (Asian Journal of Chemistry, 2014)
The cellulose superabsorbent of rice straw has been successfully synthesized using acrylic acid, acrylamide monomers as grafting agent and N-N'-methylene-bis-acrylamide as cross link then characterized using FTIR, SEM and DSC. The spectra of FTIR superabsorbent significant differences compared to that of superabsorbent copolymerization of acrylic acid-acrylamide, copolymerization of acrylic acid with acrylamide and rice straws, the differences also supported by SEM images as well as DSC spectra. The swelling capacity of superabsorbent determined in distilled water, the solution of urea, ammonium chloride and potassium di hydrogen phosphate. The swelling capacity was reached in water with up to 895.48 g/g. The swelling capacity had the following a solution of urea > water > potassium di hydrogen phosphate > ammonium chloride, this is supported by the data of rate parameter. Swelling kinetics of rice straw superabsorbent cellulose graft poly (acrylic acid-co-acrylamide) with absorbate, water, urea, potassium di hydrogen phosphate and ammonium chloride fit to the rate law pseudo second-order. This indicates the rate of swelling is proportional to the square concentration of the absorbate.